Bittorrents at mobile phones - Wong, Benjamin Ye Sheng. (2011)
Mobile phones are increasingly viewed as personal computing devices that enable access to a wide array of applications. They are increasingly becoming a means in which media is increasingly consumed and generated. This presents a need for peer to peer (P2P) applications. The P2P architecture has the advantages of reliability and reduced bandwidth cost when compared with the traditional client-server architecture. This makes the P2P model highly suitable for content distribution. By implementing P2P technology using Bittorrent, one can find, access and play multimedia contents directly from their mobile phones. The use of the PC as an intermediary can be avoided.